2020
DOI: 10.18388/pb.2019_281
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamenty: unikalne nanocząsteczki do zastosowania w biomedycynie i biotechnologii

Abstract: Nanodiamenty to bardzo drobne cząstki diamentu, które ze względu na swój rozmiar w skali nano, unikalne właściwości fizykochemiczne oraz duży stosunek łatwo modyfikowalnej chemicznie powierzchni do objętości są interesujące dla biologów, chemików i fizyków. Praca ta stanowi przegląd literatury na temat ich przygotowania, właściwości i perspektyw związanych z możliwością ich zastosowania w naukach biomedycznych. Wysoka biokompatybilność nanodiamentów, potwierdzona przez szereg badań in vivo i in vitro, odróżnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…nucleic acids, peptides, proteins, or other biologically active compounds, such as drugs. 19 One of the simplest functionali-Fig. 3 The illustration shows the synthesized nanoparticles of various shapes: (A) a sphere, (B) a cube, (C) a rod, (D) a pyramid, (E) a nanoplate, (F) an ellipse, (G) an octahedron, (H) an icosahedron, and (I) a nanostar.…”
Section: Surface Modification and Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…nucleic acids, peptides, proteins, or other biologically active compounds, such as drugs. 19 One of the simplest functionali-Fig. 3 The illustration shows the synthesized nanoparticles of various shapes: (A) a sphere, (B) a cube, (C) a rod, (D) a pyramid, (E) a nanoplate, (F) an ellipse, (G) an octahedron, (H) an icosahedron, and (I) a nanostar.…”
Section: Surface Modification and Functionalizationmentioning
confidence: 99%
“…sation methods is non-covalent functionalisation, in which the attached substances interact with the surface of nanodiamonds by electrostatic, hydrophobic, or van der Waals forces. 19 The surface of the nanoparticles is, for example, wrapped by polypeptides or other long-chain polymers. 19 After the creation processes of nanomaterials, nanoparticles most often undergo surface modification so that their physicochemical properties meet the conditions of various applications.…”
Section: Food and Function Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A new participant in the carbon nanoparticle family, nanodiamonds (NDs), is more attracted to biomedicine due to their superb chemical and physical features [65,66]. Since their initial studies in Russia in 1960, nanodiamonds have extended global consideration because of their simplistic surface modification involving excellent biocompatibility and bio-conjugation, the small size of the prime particle (about 4-5 nm) having narrow size distribution, and economic large-amount production.…”
Section: Nanodiamondsmentioning
confidence: 99%
“…Owing to small size and facile surface functionalization, NDs exhibit lower cytotoxicity and superior biocompatibility than those exhibited by other carbon materials ( Xing and Dai, 2009 ; Zhang et al, 2012 ; Qin et al, 2021 ). NDs and their derivatives have recently become interesting topics for cutting-edge research and revealed high application potential in biomedical fields, such as bioimaging, biosensing, implant coating, and drug delivery ( Shimkunas et al, 2009 ; Narayan et al, 2011 ; Haziza et al, 2017 ; Su et al, 2019 ; Fang et al, 2020 ; Jariwala et al, 2020 ; Nowicki and Czarniewska, 2020 ). In addition to the bio-related applications, NDs with reactive oxygen-containing surfaces have exhibited a certain level of antibacterial effects ( Wehling et al, 2014 ; Ong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%